Guidance And Counseling Teacher Efforts To Address Students' Sexual Behavior - Rahmi Marisha; Asmidir Ilyas (Universitas Negeri Padang, 2021)
Sexual behavior is a form of behavior in the form of holding hands, holding hands, hugging, hugging, kissing, touching sensitive areas, and intimate relationships. Previously, sexual behavior was laden with moral principles, now sex has penetrated all corners of life as a lifestyle that has zero morality even among teenagers, including students. Sexual behavior can cause various health, social, and economic problems for adolescents themselves and their families. This needs to be resolved by various parties, one of which is the school by guidance and counseling teachers through special guidance and counseling services and activities. The purpose of this study was to determine the description of students 'sexual behavior and the efforts of guidance and counseling teachers to overcome students' sexual behavior. This study used a qualitative descriptive method, with a purposive sampling technique with the number of research subjects two guidance and counseling teachers. This study uses a thematic analysis using interview transcripts that have been verbatim. The findings of this study are that there are students who have sexual behavior and the efforts provided by guidance and counseling teachers in overcoming sexual behavior, such as: providing information through classical services, conducting group guidance and group counseling services, conducting individual counseling, providing content mastery services, and doing cooperation with various parties.